OBJECTIVE PHYSICAL FUNCTION AND MENTAL HEALTH-RELATED OUTCOMES IN OLDER PRISONERS. (11th November 2018) - Barry, L; Wakefield, D; Conwell, Y; Steffens, D
Abstract: The U.S. prison population is aging; increasing numbers of older adults (age ≥50) are being incarcerated and are aging "in place." Older prisoners are likely to experience depression and suicidal ideation (SI), which are both strong predictors of suicide. However, "conventional" factors associated with increased suicide risk in mixed-age inmate samples (e.g., time served or single-cell housing) appear less relevant for older inmates. We sought to determine if physical function was associated with depression and SI in older prisoners. As part of an ongoing study, we conducted face-to-face interviews with 132 male prisoners age ≥50 from 4 Connecticut state prisons. Physical function was assessed objectively using the Short Physical Performance Battery (SPPB). The outcomes, depression and SI, were assessed using the PHQ-9 (range 0–27) and the Geriatric Suicide Ideation Scale (range 31–105); higher scores on each scale indicated worsening severity. Participants were racially diverse (42% White, 39% Black, 20% Hispanic/Other) and had a mean age of 57.2 ± 6.6 years (range 50–79 years). Using linear regression models controlling for age group (50's vs 60+), race, years in prison, and ADL difficulties, we found that increasing SPPB total score was negatively associated with depression (beta= -1.18 ± 0.30; p=0.0001), SI (beta= -0.74 ± 0.34; p=0.03), and GSIS total score (beta= -2.62 ± 0.97; p=0.008). Physical function is strongly associated with mental health outcomes in older prisoners. Using objective indicators to assess older prisoners' physical function may help to identify those who may be at higher risk of depression and SI and may indicate a target area for intervention.